Changes in the La Niña teleconnection to the Indian summer monsoon during recent period. (January 2018) - Aneesh, S.; Sijikumar, S.
Abstract: The interannual variability of Indian Summer Monsoon (ISM) rainfall is strongly associated with the El Niño–Southern Oscillation (ENSO), experiencing below and above normal rainfall during El Niño and La Niña years respectively. However, during recent La Niña years, particularly after 1980, the above normal ISM rainfall events are decreased compared to pre-1980 years. The strength of prominent monsoon circulations such as monsoon low level jet and tropical easterly jet are also decreased during recent La Niña years compared to pre-1980. In the spatial scale, the decrease in rainfall observes more over the monsoon trough region and the western part of Indian subcontinent. The number of active monsoon rainfall days, which is an identification of the intraseasonal ISM variability, are considerably reduced during post-1980 La Niña years. The warming over the Indian ocean during recent years influence the anomalous cooling observe over the western Indian ocean during La Niña events. The Indian ocean warming leads to an enhancement of convection over the equatorial region. Latent heat release from the enhanced equatorial convection warms the equatorial troposphere and weakens the meridional tropospheric temperature gradient over the monsoon region. These processes degrade the ascending motion over the Indian region, resulting weaker monsoon circulation and reduced rainfall. Highlights: Incidents of above normal Indian monsoon rainfall observe during La Nina years decrease after 1980 compared to pre-1980. Recent warming trend over the western Indian ocean changes the anomalous cooling generally observes during La Nina years. Enhanced convection over the equatorial Indian ocean weakens meridional tropospheric temperature gradient over monsoon area.